Predictors of pneumothorax following endoscopic valve therapy in patients with severe emphysema - Gompelmann, Daniela; Lim, Hyun-ju; Eberhardt, Ralf; Gerovasili, Vasiliki; Herth, Felix; Heußel, Claus Peter; Eichinger, Monika (The International journal of chronic obstructive pulmonary disease, 2016)
BACKGROUND: Endoscopic valve implantation is an effective treatment for patients with advanced emphysema. Despite the minimally invasive procedure, valve placement is associated with risks, the most common of which is pneumothorax. This study was designed to identify predictors of pneumothorax following endoscopic valve implantation. - METHODS: Preinterventional clinical measures (vital capacity, forced expiratory volume in 1 second, residual volume, total lung capacity, 6-minute walk test), qualitative computed tomography (CT) parameters (fissure integrity, blebs/bulla, subpleural nodules, pleural adhesions, partial atelectasis, fibrotic bands, emphysema type) and quantitative CT parameters (volume and low attenuation volume of the target lobe and the ipsilateral untreated lobe, target air trapping, ipsilateral lobe volume/hemithorax volume, collapsibility of the target lobe and the ipsilateral untreated lobe) were retrospectively evaluated in patients who underwent endoscopic valve placement (n=129). Regression analysis was performed to compare those who developed pneumothorax following valve therapy (n=46) with those who developed target lobe volume reduction without pneumothorax (n=83). - FINDING: Low attenuation volume% of ipsilateral untreated lobe (odds ratio [OR] =1.08, P=0.001), ipsilateral untreated lobe volume/hemithorax volume (OR =0.93, P=0.017), emphysema type (OR =0.26, P=0.018), pleural adhesions (OR =0.33, P=0.012) and residual volume (OR =1.58, P=0.012) were found to be significant predictors of pneumothorax. Fissure integrity (OR =1.16, P=0.075) and 6-minute walk test (OR =1.05, P=0.077) were also indicative of pneumothorax. The model including the aforementioned parameters predicted whether a patient would experience a pneumothorax 84% of the time (area under the curve =0.84). - INTERPRETATION: Clinical and CT parameters provide a promising tool to effectively identify patients at high risk of pneumothorax following endoscopic valve therapy.
Gesehen am 28.07.2020